2014
DOI: 10.2478/s13382-014-0280-x
|View full text |Cite
|
Sign up to set email alerts
|

A new method of determination of phases and symmetry in stand-to-sit-to-stand movement

Abstract: Objectives: Determination of the phases in a stand-to-sit-to-stand task based on a derivative of the parameter with the lowest variance calculated based on the modified symmetry index. Material and Methods: The study group comprised 11 healthy women and 11 healthy men from the University of Physical Education in Warsaw. The examination of the kinematic and kinetic parameters of sitting down and standing up from a chair was carried out using the Vicon Mx system and Kistler force platforms. Results: The modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…The sit-to-stand and stand-to-sit movements are symmetric movements [4] and, according to [5], they can be divided into two phases. In the first one, there is two contacts between the subject and the environment, which are the contact between the pelvis and the chair and the contact between the feet and the ground.…”
Section: Introductionmentioning
confidence: 99%
“…The sit-to-stand and stand-to-sit movements are symmetric movements [4] and, according to [5], they can be divided into two phases. In the first one, there is two contacts between the subject and the environment, which are the contact between the pelvis and the chair and the contact between the feet and the ground.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, some authors studied the phases of habit development during STS activity from a biomechanical aspect and used it for optimization analysis ( 16 , 21 ). The kinematic and kinetic data suggested that STS movement cycle could be divided into four or five phases ( 22 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, which specific phases are particularly crucial during the STS motion remains unclear. Previous studies on STS motion reported a wide variety of testing protocols, including difference in seat height, initial joint angle, and foot placement which led to different kinematic and kinetic results and conclusions ( 16 , 21 24 ). In addition, the kinetic and kinematic characteristics of the timing and transitional points during STS cycle were seldom explored.…”
Section: Introductionmentioning
confidence: 99%
“…Discussion:-Interpretation:-Common abilities of daily living include the capability of rising from a seated position and to sit down from a standing position (Kralj et al, 1990). STS task requires an adequate postural control and appropriate strategy in order to be performed successfully (Błażkiewicz et al, 2014).…”
Section: Figure 2 Aandb:-peak Knee Extensor Moments During Stand To Sitmentioning
confidence: 99%